Digital Tourist Storytelling and Its Impact on Tourist Visits to the Mount Mutis Nature Reserve - Goetha, Selfiana; Fallo, Apryanus; Nay , Yustina Alfira; Niha, Simon Sia (Amkop Management Accounting Review (AMAR), 2025)
This study is motivated by the low utilization of digital media in promoting natural destinations such as the Mutis Nature Reserve, despite the potential of travel narratives on social media to increase tourists' interest in visiting. The purpose of this study is to analyze the effect of Digital Tourist Storytelling on social media on Digital Tourist Engagement and Electronic Word of Mouth (E-WOM), as well as its impact on Tourists' Visiting Decisions. A quantitative approach was employed using a purposive sampling method involving 304 respondents who had previously visited Mount Mutis. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Digital Tourist Storytelling has a positive and significant effect on both Digital Tourist Engagement and Tourists' Visiting Decisions, while Digital Tourist Engagement and E-WOM also significantly influence Visiting Decisions. Indirectly, storytelling influences Visiting Decisions through Engagement and E-WOM. These findings confirm that authentic and engaging digital narratives are effective in enhancing tourist involvement, fostering positive communication, and increasing tourists' interest in visiting natural destinations.